Ruang Lingkup dan Fungsi Administrasi Pendidikan Era Society 5.0: Kajian Komprehensif dalam Perspektif Islam - Hasbi Hasidik; Elsi Retriani; Ahmad Sabri; Rully Hidayatullah (Lembaga Pengembangan Kinerja Dosen, 2024)
Educational administration has a very crucial role in managing educational institutions in various areas. This research aims to identify the functions of educational administration, the importance of this role in improving the quality of education, as well as Islamic views on education. In this study, educational administration is considered as the foundation that supports the creation of an effective and efficient education system. Apart from that, this research also explains how the Islamic view prioritizes education as a means of creating individuals who are knowledgeable and have noble morals. This journal uses qualitative methods with a literature study approach and content analysis. This research explores Islamic primary sources such as al-Qur'an and Hadith, as well as relevant secondary literature. The results of this research show that the existence of good educational administration can improve the quality of teaching and learning, which ultimately contributes to students' personal development. By understanding the importance of educational administration and the Islamic perspective on education, it is hoped that educators and administrators of educational institutions can pay more attention to these aspects in their daily practice.